Nonlinear Dynamics of the Nikkei Stock Average Futures - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1995)
This paper analyzes the conditional distribution of the Nikkei Stock Average Futures prices traded in the Singapore International Monetary Exchange (SIMEX). It is found that the conditional mean of the logarithmic price ratios is zero and the conditional variance is adequately described by the exponential generalized autoregressive conditional heteroscedasticity model (witht errors) suggested by Nelson (1991) and the autoregressive volatility model suggested by Hsieh (1993). The Brock, Dechert and Scheinkman (1987) statistic cannot reject the hypothesis that the standardized residuals are independently and identically distributed. The results are applied to calculate the maintenance margin and the long-term capital requirements of the contract given an assumed maximum failure rate. The margin requirements set by the SIMEX appear to be adequate compared to our estimates.